Adsorption and electric field assisted activation of ammonia -borane over BC3 sheet: A computational study. (8th February 2022) - Yu, Jiahui; He, Chaozheng; Huo, Jinrong; Zhao, Chenxu; Yu, Lingmin
Abstract: Using first-principles calculation within density functional theory (DFT), we studied the adsorption behavior of ammonia-borane (H3 BNH3, AB) molecule on BC3 sheet in four different solvents. We concentrated on the activation of AB adsorbed on BC3 sheet in aqueous solutions of AB with and without an external electric field (E-field). The results show that the BC3 sheet has a better activation effect on the B–H bond of AB in alkaline aqueous solutions than in a neutral aqueous solution. Compared with the metal cation (Na + or K + ), anion OH − is more conducive to the activation of the B–H bond, which is more obvious in the case of an external E-field. Under the external E-field (0.004 a.u. ), the B–H bond is elongated by about 12% compared with that of AB molecule in a free state, even if the metal cations are considered, the B–H bond is still elongated by about 10.6%. This study offers a new research method for the release of H atom in AB molecule facilitating H2 production. Graphical abstract: Image 1 Highlights: This study offers a new solution for the release of H atoms in Ammonia-borane (AB). The BC3 sheet may effectively activate AB in four different solvents. The BC3 sheet may activate AB better in alkaline aqueous solutions (NaOH, KOH) than in a neutral aqueous solution. Under the external E-field (0.004 a.u. ), the B–H bond is elongated by about 10.6%.